Methodology of social research: a toolbox - Sáenz Leandro, Ronald Andrés (2021)
Methodology of social research: a toolbox (2020), a book compilated by Mariana Caminotti and Hernán Pablo Toppi, offers an introduction to the most important themes and innovations from the methodological subfield in the area of the social sciences, in general, and political science in particular. The book is composed by 8 chapters, written by 15 authors, which go through discussions and problems that deal with the wide spectrum of social research, without delinking from diversity, challenges and debates that have characterized the methodological discussion of this profession. From a review of the main epistemological perspectives, going through conceptualization and measuring strategies and combined qualitative and quantitative research designs to the use of experiments and process-tracking apps, this book is an excellent and current reference for graduate and post-graduate studentes and teachers on these issues in Latin America.